Overtopping scour due to tsunami bore: laboratory study - Maqtan, Raidan; Yusuf, Badronnisa; Hamzah, Saiful Bahri (Walailak University, 2022)
Tsunami wave is one of the most serious threats to lives and activities, particularly in coastal cities within 100 m height from the mean sea level. Construction of coastal defense structures, such as seawalls and breakwaters, is the most popular measure adopted by engineers for protection from sea waves, including tsunamis, and mitigation of their effects. Many researchers determined through their post-tsunamis field studies that the scour at the landward toe of coastal defense structures induced by tsunami overtopping is the predominant cause of structural failures. İn the present study, a series of laboratory experiments was conducted at National Hydraulic Research Institute of Malaysia to investigate the scour profile at the landward toe of a vertical seawall induced by tsunami bore overtopping vertical seawall and examine the influence of breakwater and bore characteristics on the induced scour depth and length. The experiments showed that the breakwater in low initial depth conditions was more effective in reducing bore velocity and scour depth at the landward toe of the seawall than that in high initial depth conditions. Moreover, a strong positive relationship was confirmed between the Froude number of the overtopping flow and the induced scour depth and length.